Preterm Infant Outcomes Following COVID-19 Lockdowns in Melbourne, Australia - Brendan Mulcahy; Daniel L. Rolnik; Alexia Matheson; Yizhen Liu; Kirsten R. Palmer; Ben W. Mol; Atul Malhotra (MDPI AG, 2021)
Background Community lockdowns during the coronavirus disease 2019 (COVID-19) pandemic may influence preterm birth rates, but mechanisms are unclear. Methods We compared neonatal outcomes of preterm infants born to mothers exposed to community lockdowns in 2020 (exposed group) to those born in 2019 (control group). Main outcome studied was composite of significant neonatal morbidity or death. Results Median gestational age was 35 + 4 weeks (295 infants, exposed group) vs. 35 + 0 weeks (347 infants, control group) (p = 0.108). The main outcome occurred in 36/295 (12.2%) infants in exposed group vs. 46/347 (13.3%) in control group (p = 0.69). Continuous positive airway pressure (CPAP) use, jaundice requiring phototherapy, hypoglycaemia requiring treatment, early neonatal white cell and neutrophil counts were significantly reduced in the exposed group. Conclusions COVID-19 community lockdowns did not alter composite neonatal outcomes in preterm infants, but reduced rates of some common outcomes as well as early neonatal inflammatory markers.